Sensitivity Mapping for Electrical Tomography Using Finite Element Method - Pusppanathan, Jaysuman; Mohmad Ameran, Hanis Liyana; Hamzah, Ahmad Azahari; Abdul Rahim, Ruzairi; Abdullah, Fatin Aliah Phang; Ngadiman, Nor Hasrul Akhmal; Wahab, Yasmin Abdul (International Journal of Integrated Engineering, 2018)
This paper presents the construction of sensitivity map (SM) using finite element method for electrical tomography systems that has the soft-field characteristic such as electrical capacitance tomography (ECT). The SM is generated based on a sixteen-channel ECT system on a 110 mm diameter pipe circumference by using COMSOL Multiphysic. Sensitivity mapping is the pivotal element for tomography imaging in solving the forward problem. The obtained sensitivity map for 120 projections forming a sensitivity matrices are presented in this paper.